Effects of Mg-Palygorskite Modified Biochar on the Growth of Sedum alfredii Hance in Heavy Metal Contaminated Soil - Tianwen Wang; Xianxiang Luo; Kun Chen; Hao Zheng; Zewei Song; Lize Zhao; Junhua Gong; Fengmin Li; Ruhai Liu (Plants)
Heavy metal contamination of soil poses a serious threat to agricultural production and human health. Biochar modified with Mg and palygorskite can reduce the content of available heavy metals in soil; however, its passivation effect is affected by the modification method, and there is a lack of research on its impact on plant growth in heavily polluted soil. In this study, four types of modified biochar were prepared using MgCl2, palygorskite, and wood as raw materials, including MBC and MPB prepared by pre-modification and BCM and BPM prepared by post-modification. Sedum alfredii Hance was selected as the test plant, and a pot experiment was conducted to explore the effects of unmodified and modified biochar on the growth of Sedum alfredii Hance in heavily polluted soil with Cu, Pb, Zn, and Cd. Compared with the original biochar, the modified biochar, especially the pre-modified biochar, significantly increased the ash content, pH, O/C ratio, surface functional group count, and mineral content. The adsorption capacity for heavy metals was also significantly enhanced, with the main adsorption mechanisms being precipitation, complexation, and ion exchange. The four types of modified biochar promoted the growth and biomass of Sedum alfredii Hance to varying degrees, with the promotion effect in the order of MPB > MBC > BPM > BCM, and the effect was more significant with a 3% addition. The modified biochar significantly reduced the content of available heavy metals in the rhizosphere soil, with a passivation effect in the order of MPB > MBC > BPM > BCM, and the 3% addition had the greatest effect. Further analysis via the Mantel test and structural equation modeling confirmed that modified biochar promoted the growth of Sedum alfredii Hance by reducing the available heavy metal content in the rhizosphere soil and increasing the NO3−-N and AP contents. This study provides data support for the development of functionalized biochar for the remediation of heavy metal pollution in soil.